Flow field analysis and noise characteristics of an automotive cooling fan at different speeds - Ren, Kai; Zhang, Shuguang; Zhang, Huanping; Deng, Changming; Sun, Haiyang (Frontiers in Energy Research, 2023)
This study focuses on the analysis of flow field characteristics and noise generation in an automotive air conditioning systems, specifically related to an automobile cooling fan at different speeds. The flow field properties of the fan are examined through the distribution of flow line trajectory, pressure distribution on the blade surface, and velocity distribution characteristics at various speeds. The analysis reveals that the maximum air velocity occurs at the point where the fan blade meets the wind guard, while the maximum pressure is observed at this point and at the edge where the fan blade cuts through the cavity. Furthermore, a monitoring point located 1m in front of the fan is selected to study the average value of fan pneumatic noise pulsation and generate a noise cloud map, aiming to identify the main noise source of the fan. To better understand the noise distribution and variation at different speeds, various noise metrics are utilized, including noise Sound Pressure Level (SPL) spectrum, 1/3-octave SPL spectrum, and 1/3-octave A-weighted SPL spectrum. The noise characterization results indicate that the primary areas of fan noise generation are located at the tip of the leaf margin of the forward swept wing. This research provides valuable insights for the improvement and optimization of the cooling fan design, as well as subsequent noise reduction efforts.